CORAK ‘ILMĪ TAFSIR AL-MISBAH - Firdarini Firdarini; Moh. Anwar Syarifuddin (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to reveal portray Quranic verses interpreted using the scientific style of interpretation by M. Quraish Shihab in his Tafsir al-Misbah. Its existence has been revealed by Moh. Anwar Syarifuddin and Jauhar Azizy in their 2014 report on